KONFLIK PEMILIHAN KEPALA DAERAH KABUPATEN JEMBER TAHUN 2015 (CONFLICT OF ELECTIONS FOR DISTRICT HEAD OF JEMBER IN 2015) - Edhi Siswanto (Universitas Muhammadiyah Jember, 2017)
Jember regency is one of the areas in East Java which has a high level of political conflict escalation. This area became the center of political barometer, especially in the eastern region of East Java. So that every political development that occurs in this area will always be a big concern for every region in other areas in East Java. The research on electoral conflicts has objectives, among others: 1) to analyze the factors that cause conflict in the elections in Jember Regency in 2015, and 2) to analyze conflict resolution used in Jember District Election 2015.This type of research includes qualitative research. Data collection was done by documentation study and literature study. While the data analysis technique is an analytical descriptive technique that is done through reduction procedures, data presentation, and data verification. The result of the research shows that the conflict in Jember election in 2015 is caused by several things: (1) Faida-Muqit Arif nomination as candidate for regent and vice regent of Jember in the 2015 regional head election by the Central Board of the Indonesian Democratic Party of Struggle (PDIP). (2) Black campaign conducted by candidate pair Faida-Muqit Arif. (3) Jember KPU is Less Transparent and Open. (4) The Jember KPU is against the rule made by itself in KPU Regulation No. 8 of 2015 by passing two pairs of candidates for local heads who are late in submitting reports of campaign revenues and expenditures (LPPDK). From the results of research conducted also shows that the efforts of conflict prevention that has been done election organizer was not able to prevent the occurrence of conflict Pilkada Jember in 2015. Prevention efforts that have been done include: mapping Conflict-prone areas, monitoring activities detection and prevent early ahead of elections, coordination of regional elections and regional elections.